1998
DOI: 10.1063/1.476640
|View full text |Cite
|
Sign up to set email alerts
|

Structures and stability of hydrated clusters of hydrogen chloride, HCl(H2O)n, n=1–5

Abstract: The molecular structures of the hydrated clusters of the HCl molecule, HCl(H2O)n, n=1–5, are examined by employing density functional molecular orbital methods. The most stable structures of the n=1–3 clusters are found to be of the proton nontransferred type. In the case of the n=4 cluster, the proton nontransferred and proton transferred structures have nearly similar energies. There are several stable isomers for the n=5 case and the structures of these isomers are found to be all proton transferred. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
180
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(209 citation statements)
references
References 23 publications
25
180
2
Order By: Relevance
“…18 Re et al found that proton transfer in the hydrogen-bonded cluster HCl(H 2 O) n with n ) 1-5 completely occurs only in the case of n ) 5 clusters. 19 Using the B3LYP density functional method and the CCSD(T) ab initio method, Milet et al showed however that HCl starts dissociating already in HCl(H 2 O) 4 . 20 Devlin et al, using ab initio Monte Carlo simulations found that in HCl-(H 2 O) 6 three-coordinated HCl dissociates directly to form a clearly recognizable solvated Cl -and H 3 O + ion pair.…”
Section: Introductionmentioning
confidence: 99%
“…18 Re et al found that proton transfer in the hydrogen-bonded cluster HCl(H 2 O) n with n ) 1-5 completely occurs only in the case of n ) 5 clusters. 19 Using the B3LYP density functional method and the CCSD(T) ab initio method, Milet et al showed however that HCl starts dissociating already in HCl(H 2 O) 4 . 20 Devlin et al, using ab initio Monte Carlo simulations found that in HCl-(H 2 O) 6 three-coordinated HCl dissociates directly to form a clearly recognizable solvated Cl -and H 3 O + ion pair.…”
Section: Introductionmentioning
confidence: 99%
“…HCl(H 2 O) n and (H 2 O) n+1 clusters have similar structure and hydrogen bond strengths up to at least n = 3, after which dissociation of the acid into the ion pair is predicted to occur for the acid clusters 3,7 . The similar structures and hydrogen bond strengths of the acid and pure water clusters gives rise to similar vibrational modes.…”
Section: Resultsmentioning
confidence: 99%
“…At the MP2/6-31g(2dp) level the HCl bond length increases from the isolated molecule by 1.3% upon forming the dimer, 2.5 % for the two water cluster and 4.1% for the three water cluster . By the addition of a fourth water, the dissociated ion pair becomes the most stable product according to theory 3,7 .…”
Section: Resultsmentioning
confidence: 99%
“…One inquiry that persistently threads its way through this subject is: what is the minimum quantity of water molecules, (H 2 O) n , required to dissociate the acid [18]? According to calculations, the acidically dissociated structure is supported starting from n=4; most of the theoretical approaches agree that at this size the dissociated form represents the global minimum on the potential energy surface [18][19][20][21][22][23][24]. Experimentally, for neutral clusters the question has been probed by laser spectroscopy (see, e.g., [25][26][27][28]) but finding a conclusive spectroscopic signature of the onset of dissociation in a nanocluster is not straightforward.…”
Section: Introductionmentioning
confidence: 99%